Isu Lingkungan dalam Kumpulan Cerpen Hikayat Bunian: Kajian Ekokritik - Yulantomo, Aris; Hidayat, Rian; Nelfita, Yulia (GERAM, 2024)
This research aims to reveal: (1) environmental issues, (2) story facts, and (3) the relationship between humans and nature. This type of research is qualitative research with qualitative descriptive methods. The object of research is the short story collection Hikayat Bunian. Data collection uses reading, listening and note-taking techniques. This research uses human instruments. There are 81 data related to the formulation of research problems. The validity in this research is semantic validity, while the types of data reliability in this research are intrater and interrater. The research results are as follows. First, many environmental issues occur because human behavior and thoughts are more selfish, thus triggering actions that are detrimental to nature conservation. Second, the story facts found explain the forms of behavior and activities that destroy nature which are depicted through the characters, plot and setting. Dominant realist characters to strengthen the story. The problems are told from the start, then escalate in the middle of the story. Not all short stories have solutions and solutions to problems at the end of the story. The setting of the story is mostly set in Riau. Third, the relationship between humans and nature that is depicted tells more about the disharmonious relationship between humans and nature. This collection of short stories is a form of criticism and concern from the author regarding the actions and behavior of humans who no longer care about nature and the environment.